Features of the Construction of a Communication Strategy in The Chinese Market by The Example of Moutai - Luo Jun; Anna Korenevskaya (Communications of International Proceedings, 2021)
This paper explores the peculiarities of the Chinese communication strategy of the company in the domestic market. The Moutai brand in the alcoholic beverage market in China is regarded as the leader among the producers of the national Chinese drink - baijiu. In this study, the authors identify baijiu as an integral part of Chinese culture, which is widely used in marketing support of modern Chinese brands. The study is based on general methods, which allowed us to analyze a significant amount of literature on the topic of the article and highlight the main features that helped the Moutai brand to take a dominant position in the production and sale of spirits. Despite some problems of the Moutai brand, for example, with the registration of a trademark, it can be noted that consumer demand for Moutai baijiu only grows every year. Successful construction of the communication strategy of the brand can be explained by the existing cultural ties between the brand and the target audience, the correct positioning of the brand in the market and established distribution channels. A key factor is the brand's availability on major online marketplaces such as Taobao and Tmall, which expands the audience and dig out potential customers.
Keywords: communication; communication strategy; alcoholic beverage industry; Moutai; baijiu.